Variation in Additional Support Needs identification and support provision across schools and local authorities in Scotland - Behrens, Silvia; Treanor, Morag; Troncoso, Patricio; Russell, Emma; Lee-Shield, Bethany; Williamson, Lee; Macintyre, Cecilia (International Journal of Population Data Science, 2026)
This paper explores variation in identification of Additional Support Needs (ASN) and the provision of support across Scottish schools and local authorities. Adding to existing research on Special Educational Needs and Disabilities (SEND), this paper provides a detailed analysis of pupils’ needs and formalised support responses in the Scottish context. In Scotland, ASN legislation encompasses a broader range of needs than SEND legislation in the rest of the UK which cover social-emotional needs and needs arising from family circumstances and the learning environment. Identification of ASN carries implications for access to support in the form of co-ordinated support plans (CSP), individualised educational programmes (IEP) and Child’s Plans (CP). Using linked administrative data from the Scottish Pupil Census, education and health records and the Census, this paper addresses three research questions: (1) What are the demographic and educational characteristics of pupils identified with ASN?; (2) How does support provision for pupils vary by ASN type and across schools and local authorities?; (3) How long does it take for a pupil identified with ASN to receive an ASN support plan? We use binary logistic regression to model ASN identification and multinomial regression to assess support provision. Following a pupil cohort from the first year of primary school to the end of mandatory secondary school, we employ a longitudinal approach to investigate the trajectories from ASN identification to support provision. The findings identify disparities in support responsiveness and allocation which are relevant to address by policymakers, service providers and school staff.